Additional Legal Protection for Corruption Whistleblowers - Fardiansyah, Ahmad Irzal; Farid, Muhammad; Diansyah P, Ramadani Fitra (Universitas Lampung, 2024)
Corruption represents a breach of the economic rights of society, elevating it beyond mere criminality to the status of an extraordinary offense. Therefore, safeguarding the rights of individuals who report instances of corruption is necessary to ensure their protection. As law enforcement officers, Prosecutors hold the authority to provide legal protection to whistleblowers of corruption, as stipulated in Law Number 13 of 2006 concerning the Protection of Witnesses and Victims (LPSK). Among the various legal protections provided to whistleblowers, maintaining the confidentiality of their identity stands out as the utmost priority. This protection is crucial to ensure effective law enforcement. Hence, safeguarding whistleblowers is important, and to formalize this, law enforcement should be empowered to provide them with the necessary protection.